Dynamic subcellular compartmentalization ensures fidelity of piRNA biogenesis in silkworms. (11th May 2021) - Chung, Pui Yuen; Shoji, Keisuke; Izumi, Natsuko; Tomari, Yukihide
Abstract: PIWI‐interacting RNAs (piRNAs) guide PIWI proteins to silence transposable elements and safeguard fertility in germ cells. Many protein factors required for piRNA biogenesis localize to perinuclear ribonucleoprotein (RNP) condensates named nuage, where target silencing and piRNA amplification are thought to occur. In mice, some of the piRNA factors are found in discrete cytoplasmic foci called processing bodies (P‐bodies). However, the dynamics and biological significance of such compartmentalization of the piRNA pathway remain unclear. Here, by analyzing the subcellular localization of functional mutants of piRNA factors, we show that piRNA factors are actively compartmentalized into nuage and P‐bodies in silkworm cells. Proper demixing of nuage and P‐bodies requires target cleavage by the PIWI protein Siwi and ATP hydrolysis by the DEAD‐box helicase BmVasa, disruption of which leads to promiscuous overproduction of piRNAs deriving from non‐transposable elements. Our study highlights a role of dynamic subcellular compartmentalization in ensuring the fidelity of piRNA biogenesis. Synopsis: P‐bodies in silkworm cells harbor key piRNA factors. Dynamic exchange of piRNA factors between nuage and P‐bodies is impaired by ectopic expression of a Siwi catalytic mutant, which leads to aberrant production of mRNA‐derived piRNAs. Silkworm piRNA factors are compartmentalized into nuage and P‐bodies. Both Siwi and BmVasa catalytic activities are required for proper nuage/P‐body partitioning. Disruption of nuage/P‐body partitioning prompts mis‐production of mRNA‐derived piRNAs. Abstract : P‐bodies in silkworm cells harbor key piRNA factors. Dynamic exchange of piRNA factors between nuage and P‐bodies is impaired by ectopic expression of a Siwi catalytic mutant, which leads to aberrant production of mRNA‐derived piRNAs.